Central banking below zero: The implementation of negative interest rate policies in Europe and Japan - Stefan Angrick; Naoko Nemoto (Asian Development Bank Institute (ADBI), 2017)
This paper provides an overview of the operational implementation of negative interest rates in Europe and Japan. Drawing attention to the fact that there is precedent for negative policy rates and negative money market rates, the paper addresses conceptual issues and summarizes measures which define negative interest rate policy. Based on detailed institutional analysis and an examination of the interaction of negative interest rate policies with balance sheet policies, it is argued that there is substantial heterogeneity in the purpose, design and operational specificities of negative interest rate policies across economies, with significant consequences for effective money market rates, private sector funding conditions, and expectations. Summarizing transmission channels of negative rates to the real economy and their potential benefits and risks, the paper calls attention to potential adverse effects resulting from the interaction of negative interest rate policy with tighter liquidity and capital standards adopted since the Global Financial Crisis.
Keywords: E5; E52; E58; 330; negative interest rates; central banking; policy rates; market rates; balance sheet policies